Anthophilous beetles ubiquitously inhabit night-blooming cacti but exhibit distinct responses to the spatial distribution of flowers - ARTHUR DOMINGOS-MELO; ARTUR C.D. MAIA; PAULO MILET-PINHEIRO (Anais da Academia Brasileira de Ciências)
Abstract Night-blooming cacti, primarily pollinated by bats and hawkmoths, also attract beetles seeking food and safe shelter for mating and brooding their offspring. The influence of flower density on beetle visitation rates remains unclear, with responses varying by species and environmental factors. In the Caatinga Seasonally Dry Tropical Forest, we studied the flower occupancy distribution of two beetle species, Cyclocephala paraguayensis and Nitops aff. pilosocerei, in Pilosocereus pachycladus cacti. Our findings indicate that both beetle species act as commensals with minimal impact on effective pollination. They forage for nectar and pollen without causing damage to pistils or ovaries. N. aff. pilosocerei was more abundant than C. paraguayensis, and their distributions significantly differed, with N. aff. pilosocerei displaying a more uniform spread. Instances of both species occupying the same flower were more frequent than exclusive occupation. Nitops aff. pilosocerei abundance exhibited spatial autocorrelation. Flower height and beetle species influenced the total number of beetles within flowers. Future studies should explore the impact of cactus flower distribution on beetle abundance with other species, conduct selective pollination experiments to determine their role as pollinators, and investigate how flower-beetle interaction systems are affected by flower and individual distribution in processes like florivory and pollination.